A boy at war : a novel of Pearl Harbor - Mazer, Harry (New York : Simon & Schuster Books for Young Readers, 2001)
While fishing with his friends off Honolulu on December 7, 1941, teenaged Adam is caught in the midst of the Japanese attack and through the chaos of the subsequent days tries to find his father, a naval officer who was serving on the U.S.S. Arizona when the bombs fell.
School Library Journal.
Wilson's Junior High School.
Wilson's Senior High School.
8.5.
8.5
5-8
Keywords: Historical fiction; Pearl Harbor (Hawaii), Attack on, 1941 -- Fiction; World War, 1939-1945 -- Causes -- Fiction; Historical fiction; Pearl Harbor (Oahu, Hawaii), Attack on, 1941 -- Fiction; World War, 1939-1945 -- Causes -- Fiction; Hawaii -- History -- 1900-1959 -- Fiction; Hawaii -- History -- Fiction